(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper critically examines the judicial trends in bail decisions, with a focus on the legal and social implications of granting or denying bail. Bail, a fundamental right in many legal systems, is often subjected to judicial discretion, which significantly impacts the accused, the justice system, and society. The paper explores how judicial trends in granting bail can either reinforce or challenge the principles of equality, fairness, and the presumption of innocence, analyzing key judgments and statutory provisions that shape these practices. By studying the social consequences, including overcrowding in prisons, public perception of justice, and the effect on marginalized communities, this paper seeks to offer insights into the balancing act between individual rights and societal interests in the context of bail.